Effects of domotics on cognitive, social and personal functioning in patients with chronic stroke: A pilot study. Issue 1 (January 2020) - Maggio, Maria Grazia; Maresca, Giuseppa; Russo, Margherita; Stagnitti, Maria Chiara; Anchesi, Smeralda; Casella, Carmela; Zichitella, Caterina; Manuli, Alfredo; De Cola, Maria Cristina; De Luca, Rosaria; Calabrò, Rocco Salvatore
Abstract: Background: Stroke can cause severe brain lesions, leading to multiple cognitive, emotional and motor disorders. In fact, it is one of the main causes of death and disability worldwide, with a negative impact on quality of life for both patient and caregiver. Home automation (also known as domotics) could allow stroke patients to manage and improve their daily lives. Objective: The aim of our pilot study was to evaluate the effects of domotics on cognitive functions and personal/social autonomy in patients with stroke. Methods: We enrolled 40 patients affected by chronic stroke undergoing neurorehabilitation at IRCCS Centro Neurolesi (Messina, Italy), between June 2017 and March 2019. All of the patients were randomized into either the control group (undergoing traditional training based on face-to-face interaction between therapist and patient, and practical activities), or the experimental group (undergoing Home Automation training). Each participant was evaluated before and immediately after the training period. Each different training consisted of 3 sessions per week for eight weeks (i.e. a total of 24 sessions), each session lasting about 60 min. For both the conventional and experimental trainings, treatments were performed in groups, and all the patients were provided with the same amount of treatment. Results: Patients in the experimental group showed a greater improvement in cognitive and social performance, as compared to the control group. Conclusion: Our study shows that domotics could be effective in improving social and cognitive functioning, autonomy and functional recovery in patients affected by chronic stroke.